A Review on Wasp Venom as a Chemotherapeutic Agent in Different Types of Cancer - Sirisha, Arige; Vadapalli, Rama Rao; Srinidhi, Penmatsa; Mahalakshmi, Bathula; Yagna, Muchakarla Sri; Teja, Kanuri; Sri, T. Sowmya (International Journal of Pharmaceutical Investigation, 2026)
Cancer is the most leading cause of the death. Only few treatment options are available for treating the cancer such as radiation therapy, chemotherapy, and surgery. These treatment options can either used as single or combination therapies. Explorations of new drugs have been advanced to combat difficulties to treat cancers. New drug developments from natural biological resources are available all over the world. There are several active principles that are produced by different animals, plants and microorganisms that have been used in the development of novel drugs to combat diseases one of which is having great potential as anti-tumor agents. Wasp venom is a new productive solution that helps in treating cancers. Venoms of wasps are multifaceted mixtures of pharmacologically and biochemically functional elements like biogenic amines, peptides and proteins have been studied. Mastoparan is a selective and potent anticancer peptide. Researchers have developed a novel therapy using peptides derived from wasp venom that binds to several amino acids and show potential in cancer treatment. These peptides form pores on the cell plasma membrane and get penetrate the cell, resulting in lysis and finally causing to death. Numerous bioactive constituents were recognized from wasp venom. These peptides exhibited anticancer, antimicrobial activities against bacteria and fungi. This paper delves into recent progress in bioactive peptides and examines the prospects of utilizing wasp venom as a chemotherapeutic agent for treating variety of cancers.
Keywords: Melanoma cancer; Colorectal cancer; Breast cancer; Lung cancer; Wasp venom; Mastoparan.